Pullout Test on Fully Grouted Bolt Sheathed by Different Length of Segmented Steel Tubes - Xiaowei Feng; Nong Zhang; Guichen Li; Gangye Guo (Shock and Vibration)
In order to evaluate the anchorage performance of rebar bolt sheathed by different length of segmented steel tubes, a total of eight groups of pullout tests were conducted in this study. The steel tubes, segmented by 5 cm, 7 cm, 9 cm, 10 cm, and 15 cm, utilized in current study were bonded together by a high performance two-component adhesive to form standard 30 cm long steel tube. Unlike axial stress distribution in bolt, the axial stress distribution in steel tube showed exponential decrease trend from tube-clamp end to bolt-clamp end; thus a series of interesting results were observed. For instance, the sequence for segments detachment had its specific order of priority; the failure form of bolting system, the load oscillation characteristics, and the final displacement were highly determined by the length of the last segment, namely, the one fixed by clamp of testing machine. Moreover, the load-displacement relationship for some particular samples was further investigated from the perspective of energy transformation, and the disequilibrium extension of interfacial decoupling was also discussed. This paper, from a relatively idealized perspective, presents a laboratorial solution to interpret the mechanical performance of the bolt installed in layered strata; so far at least it demonstrates that a bolt installed in comparatively thicker layer of strata can last more durable and stable.